Budidaya dan Hilirisasi Tanaman Sorgum sebagai Komoditas Pangan Alternatif: Transformasi Menuju Kemandirian Petani di Desa Seuneubok Punti, Aceh Tamiang - Syamsul Bahri; Boy Riza Juanda; Ainul Mardiyah; Darwin Darwin (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This community service program was conducted in Seuneubok Punti Village, Manyak Payed Subdistrict, Aceh Tamiang Regency, in collaboration with the “Kloneng Jaya” Farmers’ Group. The program aimed to enhance farmers’ self-reliance and competitiveness through the development of sorghum cultivation and downstream processing based on appropriate technology. The main challenges faced by the partners included limited crop diversification, inadequate technical cultivation capacity, underdeveloped post-harvest processing, weak business management, and limited market access. The program was implemented using a participatory extension approach through counseling, technical training, demonstration plots, field mentoring, technology transfer, and continuous evaluation of program achievements. Interventions included agroecology-based sorghum cultivation training, establishment of demonstration plots, post-harvest processing into value-added products, formation of a Joint Business Group, and development of digital marketing strategies. The results demonstrated significant achievements, including the establishment of a 0.5 ha demonstration plot, an increase in farmers’ technical capacity of more than 80%, the availability of processed sorghum products (rice, flour, and derivative products), the establishment of a farmers’ economic institution, and the implementation of digital marketing practices. The program contributed positively to income generation, institutional strengthening, technology adoption, and environmentally friendly agricultural practices. The integrated upstream–downstream approach proved effective in transforming farmers into more independent, productive, and sustainable agribusiness actors while supporting local food diversification and rural economic development.